Neuromuscular electrical stimulation of the quadriceps in patients with non-small cell lung cancer receiving palliative chemotherapy: a randomized Phase II study - Lucia, Alejandro; Maddocks, Matthew; Halliday, Vanessa; Chauhan, Alpna; Taylor, Victoria; Nelson, Annmarie; Sampson, Cathy; Byrne, Anthony; Griffiths, Gareth; Wilcock, Andrew (Public Library of Science, 2013)
Background